Rags in the High Rent District: The Evolution of Quota Rents in Textiles and Clothing - Joseph F. Francois; Julia Wörz (The Vienna Institute for International Economic Studies (wiiw), 2006)
We develop a mixed complementarity programming (MCP) based estimating framework for non-tariff barriers (NTBs) to examine the evolution of market access conditions in the textile and clothing sectors, working with a panel of bilateral trade data on textile and clothing trade, underlying bilateral tariffs, and the country-pair coverage of quotas under the WTO's Agreement on Textiles and Clothing (ATC). Our estimating framework takes advantage of the panel nature of trade data when calculating export tax equivalents while allowing for inequality constraints on the quota premium estimates. We also introduce Gaussian quadrature for estimating goodness of fit for regression-based NTB measures based on residual fitting.
Keywords: F13; C15; 330; NTB estimation; Gaussian quadrature; quotas; ATC; MFA